Methicillin-resistant Staphylococcus aureus in cows with mastitis, the presence of the mecA gene and the gene for virulence - Vesna Jaki Tkalec; Darko Majnarić; Jadranka Jurmanović; Boris Habrun; Željko Cvetnić; Manuela Zadravec; Branka Šeol Martinec (Mljekarstvo)
The physiological properties of 47 Staphylococcus aureus strains were investigated. The test strains were grown on bacteriological media and identified by the ID32 STAF system for biochemical identification of bacteria. Sensitivity to antimicrobial agents was performed by the disc diffusion method. The nuc gene and the virulence factors coa, hla, hlb, hld, hlg, hlg-2, tst, eta, etb, lukF-PV and lukS-PV and mecA gene were detected by the polymerase chain reaction. Furthermore, the spa type of the studied isolates was also set. According to the obtained results, all strains had the nuc, coa, hla and hld gene. Ten strains (21.3 %) had also the tst gene, while 37 strains (78.7 %) had the hlg gene and 35 strains (74.5 %) had the hlb and hlg-2 genes. All of the investigated S. aureus isolates were penicillin resistant (100 %), with 29 strains which were also resistant to oxacillin (61.7 %). Methicillin (oxacillin) resistance was detected by the mecA gene detection, which is also the first MRSA result from the secretion samples of cows’ mammary glands in Croatia. The researched MRSA strains proved to belong to different spa types, and the most common were spa types t005, t011 and t521, and a new spa type t9498 was detected.